2015
DOI: 10.1038/sc.2015.120
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and cardiovascular responses to treadmill walking and stationary cycling in subjects with incomplete spinal cord injury

Abstract: Study design: Randomized controlled trail. Objectives: To investigate if people with incomplete spinal cord injury (SCI) can perform high-intensity weight-bearing exercise by comparing cardiovascular responses at maximal workloads during stationary cycling and treadmill walking, and to explore mechanical efficiencies at sub-maximal workloads. Setting: Sunnaas Rehabilitation Hospital, Nesoddtangen, Norway. Methods: Fifteen people with incomplete SCI and 15 healthy control subjects performed sub-maximal and maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…6 Although there has been substantial emphasis on the neuromuscular 7-9 and cardiovascular 10,11 adaptations following rehabilitation, adaptations of the pulmonary system of individuals with incomplete SCI (iSCI) in response to locomotor training have been less frequently studied.…”
Section: Introductionmentioning
confidence: 99%
“…6 Although there has been substantial emphasis on the neuromuscular 7-9 and cardiovascular 10,11 adaptations following rehabilitation, adaptations of the pulmonary system of individuals with incomplete SCI (iSCI) in response to locomotor training have been less frequently studied.…”
Section: Introductionmentioning
confidence: 99%
“…Mean VO 2peak measured in the present study was similar to that found in previous studies of wheelchair ergometry and ACEs. 15,19,[35][36][37] Two previous studies 16,33 reported higher VO 2peak values than the present study, possibly reflecting the difference in sample populations; Torhaug and colleagues tested persons with paraplegia, and Wouda and colleagues focused on adults with SCI with an ASIA D classification. As 70% of participants from the present study had tetraplegia, we would expect mean VO 2peak values to be lower, as less active muscle mass yields lower metabolic rates.…”
Section: Discussionmentioning
confidence: 47%
“…These differences in speed may have resulted in higher RPE ratings for the same 30 W workload. 16,33 The ACE also required participants to use an unfamiliar cranking motion and activate the trunk and/ or upper extremity muscles to maintain an upright posture during testing. Wheelchair seating position is critical for lung function and activity performance for individuals with SCI, particularly those with tetraplegia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations